Diasporic Identity and War Trauma: A Traumatic Study of Red Birds - Ahmed; Dr. Rasib Mahmood (International Journal of Business and Economic Affairs, 2024)
This study looks into the psychological impact of war trauma and diasporic identities resulting from the complexities of war. This research explores how characters grapple with the feelings of diaspora by applying concepts like mimicry, hybridity, and ambivalence. The novel depicts the survival of characters in a harsh burning desert in the merciful hands of segregated locals. This devastating experience forces them to witness life from the perspective of those they may have previously seen as “the Other” and to confront their own identity. This exposure creates a rich platform for applying Homi K. Bhabha's theories and reader-response theory to understand the protagonist's evolving sense of self in this wartorn world.